(untitled) (International Journal of Environmental Sciences, 2025)
Posterior Reversible Encephalopathy Syndrome (PRES) is a rare but potentially reversible neurological condition characterized by seizures, altered mental status, and specific radiological findings. Though often associated with hypertensive emergencies, it can also occur in normotensive postpartum women. The coexistence of PRES with stress-induced cardiomyopathy and postpartum psychosis is exceedingly rare and clinically challenging. We report a rare case of a 21-year-old primigravida at 36+3 weeks gestation with an uneventful antenatal course who underwent emergency cesarean section for decreased fetal movements and suspected leaking per vaginum. On postoperative day 1, she developed generalized tonic-clonic seizures without preceding hypertension or eclampsia. MRI brain revealed findings consistent with PRES. Severe hyponatremia (Na: 114 mmol/L) was identified as a likely precipitating factor. On postoperative day 3, she developed paranoid delusions, auditory hallucinations, and disturbed sleep, suggestive of postpartum psychosis. She was managed in the intensive care unit with antiepileptics, correction of hyponatremia, and antipsychotic therapy. A multidisciplinary approach led to gradual recovery. This case highlights the clinical complexity of PRES presenting alongside stress-induced cardiomyopathy and postpartum psychosis in a normotensive patient. Early neuroimaging, correction of metabolic derangements, and psychiatric evaluation are essential for timely diagnosis and management. High clinical suspicion and multidisciplinary care are crucial for favorable outcomes in postpartum neurological emergencies.